The Meaning of Happiness among Urban Children and Adolescents in Indonesia: A Qualitative Study Through Drawings - Handayani, Eko; Maulina, Dewi; Dahlan, Winarini W (Psychological Research on Urban Society, 2025)
Urban children and adolescents face various stressors, including academic pressure, digital media exposure, and limited green spaces, which influence their happiness perception. This study aims to explore the meaning of happiness in children and adolescents living in Indonesia’s urban areas through qualitative research using a drawing-based approach. A total of 243 participants, aged 9-15, from elementary and junior high schools in Jakarta, were asked to draw "I am happy when..." with written brief explanations. Data were analyzed using visual and narrative-thematic approaches across children and adolescents from a developmental psychology perspective. The findings reveal that the images and explanations of the drawings yield eight themes. Six themes (solitary, relational, naturalistic, material, altruistic, and wish-based happiness) emerged in both groups, while two themes (being free from problems and achievement) appeared only in the drawings of the adolescents. This study shows developmental differences in how happiness is perceived and expressed across age, gender, and contextual influences in urban settings. These insights can help educators, mental health professionals, and parents better understand the worlds of children and adolescents and design developmentally appropriate programs that support their happiness through symbolic expression.